Neural substrates of affective temperaments: An intersubject representational similarity analysis to resting‐state functional magnetic resonance imaging in nonclinical subjects - Qiu, Yidan; Wu, Xiaoyan; Liu, Bingyi; Huang, Ruiwang; Wu, Huawang (Human brain mapping, 2024)
Previous research has suggested that certain types of the affective temperament, including depressive, cyclothymic, hyperthymic, irritable, and anxious, are subclinical manifestations and precursors of mental disorders. However, the neural mechanisms that underlie these temperaments are not fully understood. The aim of this study was to identify the brain regions associated with different affective temperaments. We collected the resting‐state functional magnetic resonance imaging (fMRI) data from 211 healthy adults and evaluated their affective temperaments using the Temperament Evaluation of Memphis, Pisa, Paris and San Diego Autoquestionnaire. We used intersubject representational similarity analysis to identify brain regions associated with each affective temperament. Brain regions associated with each affective temperament were detected. These regions included the prefrontal cortex, anterior cingulate cortex (ACC), precuneus, amygdala, thalami, hippocampus, and visual areas. The ACC, lingual gyri, and precuneus showed similar activity across several affective temperaments. The similarity in related brain regions was high among the cyclothymic, irritable, and anxious temperaments, and low between hyperthymic and the other affective temperaments. These findings may advance our understanding of the neural mechanisms underlying affective temperaments and their potential relationship to mental disorders and may have potential implications for personalized treatment strategies for mood disorders. We employed intersubject representational similarity analysis to identify the brain regions associated with affective temperaments, which are considered subclinical manifestations and precursors of mental disorders, particularly bipolar disorder. The study revealed that depressive, cyclothymic, irritable, and anxious temperaments exhibited similar brain activity patterns, while the hyperthymic temperament displayed distinct activity patterns.